2015
DOI: 10.1038/nn.4060
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Vav2-dependent mechanism for GDNF/Ret control of mesolimbic DAT trafficking

Abstract: Dopamine (DA) homeostasis is essential for a variety of brain activities. Dopamine transporter (DAT)-mediated DA reuptake is one of the most critical mechanisms for normal DA homeostasis. However, the molecular mechanisms underlying the regulation of DAT activity in the brain remain poorly understood. Here we show that the Rho-family guanine nucleotide exchange factor protein Vav2 is required for DAT cell surface expression and transporter activity modulated by glial cell line-derived neurotrophic factor (GDNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 60 publications
1
44
0
Order By: Relevance
“…Recent studies using genetic amplification of GDNF levels with spatially unchanged localization [327], show that GDNF increases DA neuron number in midbrain and terminals in striatum, and increases DA content; unsurprisingly then, striatal DA release and uptake are increased in these mice [327]. The role of GDNF and Ret signaling does not end there, as GDNF acting via Ret also regulates DAT surface expression in a given cell, in a signaling cascade that involves the Rho-family guanine nucleotide exchange factor protein, Vav2 [328]. Mice deficient in either Vav2 or Ret have elevated DAT activity in the NAc, suggesting that GDNF is a key determinant of DAT trafficking in vivo and contributes DA homeostasis [328].…”
Section: Regulation Of Dopamine Releasementioning
confidence: 99%
“…Recent studies using genetic amplification of GDNF levels with spatially unchanged localization [327], show that GDNF increases DA neuron number in midbrain and terminals in striatum, and increases DA content; unsurprisingly then, striatal DA release and uptake are increased in these mice [327]. The role of GDNF and Ret signaling does not end there, as GDNF acting via Ret also regulates DAT surface expression in a given cell, in a signaling cascade that involves the Rho-family guanine nucleotide exchange factor protein, Vav2 [328]. Mice deficient in either Vav2 or Ret have elevated DAT activity in the NAc, suggesting that GDNF is a key determinant of DAT trafficking in vivo and contributes DA homeostasis [328].…”
Section: Regulation Of Dopamine Releasementioning
confidence: 99%
“…The heterologous nature of DAT expression here indicates that Src effects are not linked to changes in DAT transcription from its endogenous promoter, reminding us of the posttranscriptional mechanisms engaged by Src to modulate SERT in the same study. Recently, Zhu et al (2015) identified a GDNF/Ret signaling pathway that influences DAT trafficking in the nucleus accumbens, mediated by the Rho family guanine exchange factor Vav2. GDNF stimulation of heterologously expressed DAT/Ret (N2A cells) resulted in reduced transporter surface expression, with no change in total DAT levels and decreased DA uptake.…”
Section: B Evidence For Endogenous Pathways Triggering Regulation Ofmentioning
confidence: 99%
“…Although the functions of Vav proteins in the nervous system are far from clear, several studies have found critical roles for Vav family members in nervous system function. For example, Vav proteins have been shown to be important for axonal development (Cowan et al 2005;Malartre et al 2010;Sauzeau et al 2010a;Fernandez-Espartero et al 2013), synaptic plasticity (Hale et al 2011), and negative regulation of sympathetic nervous system activity (Sauzeau et al 2006(Sauzeau et al , 2007(Sauzeau et al , 2010b(Sauzeau et al , 2011Zhu et al 2015). Moreover, Vav3 has been identified as a candidate schizophrenia gene (Ikeda et al 2011;Aleksic et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our studies confirm the notion that the second, prolonged bout of sleep-like behavioral quiescence is critical for cellular homeostasis because the rescued animals, unlike vav-1 mutants, showed wild-type survival after exposure to noxious heat stress. , 2010bZhu et al 2015). Moreover, Vav3 has been identified as a candidate schizophrenia gene (Ikeda et al 2011;Aleksic et al 2013).…”
mentioning
confidence: 99%